Below or all the way to the peak? Oxygen uptake efficiency slope as the index of cardiorespiratory response to exercise—the NOODLE study - Kasiak, Przemysław; Kowalski, Tomasz; Rębiś, Kinga; Klusiewicz, Andrzej; Starczewski, Michał; Ładyga, Maria; Wiecha, Szczepan; Barylski, Marcin; Poliwczak, Adam Rafał; Wierzbiński, Piotr; Mamcarz, Artur; Śliż, Daniel (Frontiers in Physiology, 2024)
Background: The ratio of oxygen uptake (VO2) to minute ventilation (VE) is described as the oxygen uptake efficiency slope (OUES). OUES has been suggested as a valuable submaximal cardiorespiratory index; however, its characteristics in endurance athletes remain unknown. In this study, we a) investigated OUES between different time intervals, b) assessed their prediction power for VO2peak, and c) derived new prediction equations for OUES tailored for well-trained individuals. Materials and Methods: A total of 77 male (age = 21.4 ± 4.8 yrs; BMI = 22.1 ± 1.6 kg·m−2; peak oxygen uptake = 4.40 ± 0.64 L·min−1) and 63 female individuals (age = 23.4 ± 4.3 yrs; BMI = 23.1 ± 1.6 kg·m−2; peak oxygen uptake = 3.21 ± 0.48 L·min−1) underwent the cycling cardiopulmonary exercise test. OUES was measured at 75%, 90%, and 100% of exercise duration. Prediction power and new models were derived with the multiple linear regression method. Results: In male subjects, OUES [mL·min−1/L·min−1] from 75% = 4.53 ± 0.90, from 90% = 4.52 ± 0.91, and from 100% = 4.41 ± 0.87. In female subjects, OUES [mL·min−1/L·min−1] from 75% = 3.50 ± 0.65, from 90% = 3.49 ± 0.62, and from 100% = 3.41 ± 0.58. OUES did not differ between time intervals in male (p = 0.65) and female individuals (p = 0.69). OUES strongly predicts peak VO2 independently from the measuring interval (β = 0.71–0.80; R2 = 0.50–0.63). The prediction model designed for elite athletes was OUES [mL·min−1/L·min−1] = −1.54 + 2.99; BSA [m2]—0.0014; (age [in years]; sex [1 = male, 2 = female]) (R2 = 0.36). Conclusion: OUES enables an accurate prediction of peak cardiorespiratory fitness in elite endurance athletes. OUES is a feasible alternative to maximal exercise testing. A new prediction equation should be used for highly trained individuals. Physicians should understand OUES physiology to properly assess the cardiorespiratory response to exercise in athletic cohorts.